Liczby graniczne zanieczyszczenia gleb w polityce proekologicznej państwa = Soil contamination threshold values as element of the pro-ecological state politics - Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Economy with soil resources, as with part of natural environment, bases oneself on qualification of their quality. Most often this is perceived as comparison of real situation to the limit values. Work presents mechanisms of constructing of soils threshold values, leaning in a modern manner not only on natural science, but also on policy, economy and sociology.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)